The information content of operations-related disclosures. Issue 1 (December 2019) - Ma, Guang
Abstract: This study examines the information content of firms' operations-related disclosures (ORDs) and the importance of these disclosures as an information source to stock markets relative to other commonly examined sources of information. I find that ORDs constitute a large portion of corporate press releases. These disclosures are associated with significant stock price reactions and trading volume. The stock price reactions to ORDs are greater than the reactions to 10-K/Q reports and are of similar magnitudes to the reactions to 8-K filings. On average, ORDs explain variation in firms' quarterly returns to a similar degree as management earnings forecasts and 10-K/Q reports for the full sample and to a greater degree for small firms and firms with lower earnings quality.